SUBJECTS OF METHOD: ELEMENTARY REFLECTIONS ON THE DIALETIC MATERIALISM. (Fiep Bulletin - online, 2015)
The Marxist''s concepts seek to wake up the interest for the need of a larger deep studies of the Marxist theory and as the method adopted by Marx. It allows a better reading and understanding of the concrete reality.The objective is to contemplate the foundations of the method dialetics materialistic . Elementary notions of knowledge's method. The foundations of the dialetics materialistic's method. Presupposes and beginning of the determination. Formal logic and dialetic logic . The dialetic logic, the laws of the matter's dialetic movement. The dialetic method and the education methodologies. It is a bibliographical study. Concluding the Dialetic Materialism allows the working class become emancipated of the spiritual slavery in that the oppressed classes vegetativing, because it shows a new vision of the world, that takes to man's freedom. Looking for understand the society of your time well and better, Marx extended the beginnings of dialetic materialism to the study of social life, applying those beginnings to the social phenomena, creating a new discipline - the Historical Materialism.
Keywords: materialism; dialetics and method.